Promoting the social and emotional wellbeing of West Kimberley Aboriginal children and youth - Omari, Melinda Claire (Curtin University, 2008)
Aboriginal young people experience a high rate of family violence, alcohol and drug misuse, suicide, sexual abuse, and socioeconomic disadvantage (Gordon, Hallahan & Henry, 2002; Hunter, 1990, 1991c; Kimberley Aboriginal Medical Services Council, 1999; Memmott, Stacy, Chambers & Keys, 2001; Swan & Raphael, 1995). Over the last decade a burgeoning array of policy, services and programs have been developed to combat the social and emotional problems in Aboriginal communities. Despite some successes, Aboriginal children and youth consistently demonstrate poorer outcomes than non-Aboriginal youngsters across most domains of living, including health, mental health, education and vocation (Zubrick et al., 2005). While the evidence-base related to problems in Aboriginal communities has expanded, there is a deficit in knowledge about practical and sustainable interventions to build strengths in remote young Aboriginal people and families, to promote youth and community wellbeing. Even less has been done on the ground to assist remote Aboriginal communities to take action in tackling the problems they face (Atkinson, Bridge & Gray, 1999; Kimberley Aboriginal Medical Services Council & Westerman, 2002; National Aboriginal Health Strategy Working Party, 1989).This qualitative participatory action research project conducted in the West Kimberley Western Australia from 2001 to 2004 was in collaboration with agencies based in Broome and the Bardi people of Ardyaloon Community, One Arm Point. The investigation aimed to (1) identify and explain the mental health and social and emotional problems affecting Aboriginal young people and families living in remote communities in the West Kimberley; and (2) identify and describe goals and methods for intervention to promote social and emotional wellbeing and build resilience in young people and communities. The third aim was to feed back and culturally validate the research findings. The overarching goal of this project was to work in partnership with Ardyaloon Community in prioritising community-based solutions to youth problems. An Aboriginal Project Advisory Group was formed to guide the research and several local project assistants were employed to assist with the field work. The project involved three studies. Overall, 32 Broome-based youth, parents and service providers, and 59 Elders, parents, youth and service providers from One Arm Point were involved in interviews and discussion groups. The findings were discussed and validated by 101 agency and community people. The results indicate a number of risk and resilience factors operating across the individual, family, community and socio-political sphere, including cultural and historical factors influencing youth wellbeing. From the findings, a model for community-based mental health promotion intervention was developed to address youth problems and build strengths prioritised by Ardyaloon Community.